Penerapan Akuntansi Lingkungan dalam Pengolahan Limbah Botol Plastik di SDI Lisabheto - Theresa Yuliana Jaeng; Katharina Yuneti; Wihelmina Maryetha Yulia Jaeng (Jurnal Riset Akuntansi, 2025)
Global environmental issues demand early awareness, including in environmental accounting. This study aims to improve SDI Lisabetho students' understanding of environmental accounting concepts and desires through community education and mediation. An interactive approach is applied by practicing processing plastic bottle waste into plant pots, providing direct experience of the importance of protecting the environment. The results of the study showed an increase in students' awareness of the environmental impacts of economic activities and the role of individuals in desires. In addition, students better understand how accounting reporting can include social and environmental aspects. The implications of this study emphasize the importance of integrating environmental accounting education into the elementary school curriculum to form a generation that cares about the environment and has a deep understanding of environmental accounting. Thus, it is hoped that students can adopt environmentally friendly habits, contribute to maintaining a balance between the economy, society, and ecology, and have critical awareness of the long-term impacts of economic activities on the environment. Introducing environmental accounting from an early age can also be a strategic step in creating a more responsible and sustainable society in the future.